Pengaruh Tingkat Pemahaman Dan Kesiapan Pelaku Umkm Terhadap Implementasi Sak Emkm Pada Umkm Di Kecamatan Telanaipura Kota Jambi - Nadia Ladita; Putri Apria Ningsih; Nurfitri Martaliah M E K (JOURNAL SAINS STUDENT RESEARCH, 2023)
Financial reports have the aim of providing information on the financial position, financial performance and cash flow reports of an entity that is useful for a large number of users in making economic decisions by anyone who is not in a position to request special financial reports to meet these information needs. Research with the title "The Influence of the Level of Understanding and Readiness of MSME Actors on the Implementation of Sak Emkm on MSMEs in Telanaipura District, Jambi City". This research uses a quantitative type of research. The data sources used are primary data and secondary data. With a sample of 76 respondents in the Telanaipura sub-district, Jambi City. The results obtained in this research show that the variable level of understanding and level of readiness together have a significant influence on the implementation of SAK EMKM in MSMEs in Telanaipura District, Jambi City